2022
DOI: 10.1111/1365-2664.14218
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic population decrease due to invasive species predation in a long‐lived seabird supports need for eradication

Abstract: Invasive species are one of the greatest drivers of biodiversity loss worldwide, and the eradication of invasive species from islands is a highly efficient management strategy. Because eradication operations require large financial investments, uncertainty over the magnitude of impacts of both invasive species and their removal can impede the willingness of decision makers to invest in eradication. Such uncertainty is prevalent for long‐lived species that display an inherent lag between life stages affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Seabird populations also include substantial ‘unobservable’ life history stages (pre-breeding juveniles, non-breeding adults) that strongly affect population viability but are difficult to monitor directly because these stage classes are absent from colonies at the time of the count. For example, demographic monitoring of Tristan albatross ( Diomedea dabbenena ) revealed that reproductive failure diminished the abundance of unobservable (non-breeding and pre-breeding) stage classes across an 18-year period, despite apparent stability in the number of observable breeders [ 53 ]. Because we are similarly capturing a subset of the population (and in our case, not the breeding population), the framework we present here may represent an index of demographic parameters for emperor penguins, such as breeding success, of which sustained changes would ultimately influence the unobservable breeding population of emperor penguins (during austral winter).…”
Section: Resultsmentioning
confidence: 99%
“…Seabird populations also include substantial ‘unobservable’ life history stages (pre-breeding juveniles, non-breeding adults) that strongly affect population viability but are difficult to monitor directly because these stage classes are absent from colonies at the time of the count. For example, demographic monitoring of Tristan albatross ( Diomedea dabbenena ) revealed that reproductive failure diminished the abundance of unobservable (non-breeding and pre-breeding) stage classes across an 18-year period, despite apparent stability in the number of observable breeders [ 53 ]. Because we are similarly capturing a subset of the population (and in our case, not the breeding population), the framework we present here may represent an index of demographic parameters for emperor penguins, such as breeding success, of which sustained changes would ultimately influence the unobservable breeding population of emperor penguins (during austral winter).…”
Section: Resultsmentioning
confidence: 99%
“…However, as for most seabirds, both partners contribute to raising the chicks, and therefore, negative impacts on one sex could be expected to reduce reproductive success ( Schreiber and Burger, 2001 ). While cormorants, as long-lived seabirds, are resistant to occasional breeding failure, repeated failures can be expected to eventually impact demography and population sizes ( Oppel et al, 2022 ; Schreiber and Burger, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seabirds are highly sensitive to environmental changes and significant modifications of their biology in response to climatic [40] and anthropogenic changes, such as habitat modifications and alien predator introductions [41], have been described. Seabird numbers have decline by 70% over the past 60 years, with the highest decreased reported for terns (86%; [42]).…”
Section: Discussionmentioning
confidence: 99%